Distinguishing climate change worry from state climate anxiety across 32 countries: implications for subjective wellbeing - Eun Hee Lee; Charles Adedayo Ogunbode; Sibele Aquino; Navjot Bhullar; Mai Albzour; Rahkman Ardi; Arin H. Ayanian; Aydin Bayad; Laura Martinez Buelvas; Razieh Chegeni; JohnBosco Chika Chukwuorji; Rouven Doran; et al. (Journal of Environmental Studies and Sciences, 2026)
The concepts of “climate change worry” and “climate change anxiety” are often used interchangeably in climate research, but they may reflect distinct emotional responses to climate change, which could potentially have different implications for public mental health. This research brief aims to empirically examine the differences between these two constructs by comparing their associations with key indicators of subjective wellbeing. Using survey data from 32 countries ( N = 12,246), we compared how strongly climate change worry and state climate anxiety were each associated with subjective wellbeing, as measured by the WHO-5 Wellbeing Index and life satisfaction. State climate anxiety showed stronger associations with both WHO-5 Wellbeing Index and life satisfaction than climate change worry. This underscores the importance of treating the two as distinct emotional responses, each with different implications for public wellbeing. These insights are especially relevant for policymakers and climate communicators, who must carefully consider the emotional tone of climate messaging to foster constructive engagement while safeguarding the psychological wellbeing of the public.